2019
DOI: 10.1002/ejic.201801503
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of the Phospha‐ and Arsaethynolate Anions, PCO and AsCO

Abstract: The anions PCOand AsCOare shown to be electroactive and are studied in aqueous and non-aqueous solutions. Cyclic voltammetry is used to extract fundamental physicochemical parameters such as oxidation peak potentials, and transfer and diffusion coefficients of the anions to better understand the nature of the oxidation process. Variation of the potential scan rate reveals that electro-oxidation of PCOwith the release of CO is controlled by diffusion and is a one-electron [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Compton and Goicoechea et al studied the electrochemical oxidation of the OCP − anion in aqueous solution where they observed that the current increased linearly with the square root of the scan rate in a diffusion-controlled process. 109 Cyclic voltammograms were recorded by varying the potential from 0.0 V to 1.1 V and back to 0.0 V ( vs. an Ag reference) using glassy carbon (GC) as the working electrode (0.1 M KCl), Pt-sponge as the counter electrode and Ag as a pseudo-reference electrode in a deoxygenated solution of 2.0 mm [Na(dioxane) x ](OCP) in 0.1 M KCl. The result was compared with reported irreversible oxidation of [Na(dioxane) x ](OCP) in DMSO containing t Bu 4 NBF 4 as electrolyte.…”
Section: Applications Of Ocp− and Ocas− Anionsmentioning
confidence: 99%
“…Compton and Goicoechea et al studied the electrochemical oxidation of the OCP − anion in aqueous solution where they observed that the current increased linearly with the square root of the scan rate in a diffusion-controlled process. 109 Cyclic voltammograms were recorded by varying the potential from 0.0 V to 1.1 V and back to 0.0 V ( vs. an Ag reference) using glassy carbon (GC) as the working electrode (0.1 M KCl), Pt-sponge as the counter electrode and Ag as a pseudo-reference electrode in a deoxygenated solution of 2.0 mm [Na(dioxane) x ](OCP) in 0.1 M KCl. The result was compared with reported irreversible oxidation of [Na(dioxane) x ](OCP) in DMSO containing t Bu 4 NBF 4 as electrolyte.…”
Section: Applications Of Ocp− and Ocas− Anionsmentioning
confidence: 99%